Disparities in Pancreatic Cancer Treatment and Outcomes - Marcus Noel; Kevin Fiscella (Mary Ann Liebert, 2019)
Purpose: Pancreatic cancer remains a major health concern; in the next 2 years, it will become the second leading cause of cancer deaths in the United States. Health disparities in the treatment of pancreatic cancer exist across many disciplines, including race and ethnicity, socioeconomic status (SES), and insurance. This narrative review discusses what is known about these disparities, with the goal of highlighting targets for equity promoting interventions. Methods: We performed a narrative review of health disparities in pancreatic cancer spanning greater than ten areas, including epidemiology, treatment, and outcome, using the PubMed NIH database from 2000 to 2019 in the Unites States. Results: African Americans (AAs) tend to present at diagnosis with later stage disease. AAs and Hispanics have lower rates of surgical resection, are more likely to be treated at low volume hospitals, and often experience higher rates of morbidity and mortality compared to white patients, although control for confounders is often limited. Insurance and SES also factor into the delivery of treatment for pancreatic cancer. Conclusion: Disparities by race and SES exist in the diagnosis and treatment of pancreatic cancer that are largely driven by race and SES. Improved understanding of underlying causes could inform interventions.